Metformin suppresses the esophageal carcinogenesis in rats treated with NMBzA through inhibiting AMPK/mTOR signaling pathway. (16th November 2018) - Fan, Hongjun; Yu, Xiying; Zou, Zhigeng; Zheng, Wei; Deng, Xin; Guo, Liping; Jiang, Wei; Zhan, Qimin; Lu, Shih-Hsin
Abstract : Metformin showed chemopreventive effect on the carcinogenesis of ESCC induced by NMBzA in rats. Treatment with metformin led to activation of AMPK and attenuated the downstream signaling molecules such as mTOR, p-p70S6K and cyclin D1 in both rat precancerous lesions and tumors induced by NMBzA in vivo and human ESCC cells in vitro . Abstract: Metformin is a widely used antidiabetic drug for the management of type 2 diabetes mellitus. Recently, epidemiological studies demonstrate that metformin has anticancer effects on esophageal squamous cell carcinoma (ESCC) and other cancers. However, the effects and potential mechanisms of metformin on ESCC remain elusive. In this study, we used N -nitroso- N -methylbenzylamine (NMBzA), a special carcinogen for esophagi, to develop a rat ESCC model, in which the carcinogenesis progression of ESCC in rat was induced and promoted. We investigated the effects of metformin on carcinogenesis of ESCC in this model. Our results revealed that metformin significantly decreased the incidence and precancerous lesions of ESCC and inhibited proliferation and promoted apoptosis of esophageal epithelial cells in rat treated with NMBzA. Moreover, metformin also increased apoptosis and inhibited migration, colony formation and tumor sphere formation of human ESCC cells in vitro . Immunohistochemistry and western blotting showed that without interfering the metabolism of NMBzA, metformin inhibited the inflammation of esophagi via reducing the expressions of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) and interleukin-6 (IL-6). Treatment of metformin led to activation of AMP-activated protein kinase (AMPK) and attenuated signaling of the downstream molecules such as p-mTOR, p-p70S6K and cyclin D1 expression both in vivo and in vitro . Taken together, our study demonstrated that metformin suppressed the carcinogenesis of ESCC through inhibiting AMPK/mammalian target of the rapamycin (mTOR) signaling pathway, resulting in its chemopreventive effects on the carcinogenesis of ESCC.